Sosialisasi Sekunder BPJS Ketenagakerjaan Sebagai Upaya Dalam Peningkatan Brand Awareness Bagi Pelaku UMKM Kelurahan Medokan Ayu Surabaya - Khotija Hadi Ningrum; Bowo Santoso (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
Based on reports related to these work accidents and most of them occur in the traders, goods, and consumption industries which are also micro-business or commonly referred to as UMKM social protection needs to be carried out for the Indonesian people in the form of social security. Indonesia has 64,197,050 UMKM that are recorded by the Ministry of Cooperatives UMKM so Indonesian workers who work as UMKM are classified as many and each worker needs social security protection from the government to avoid work accidents as happened before. Therefore, these problems are resolved using observation and interview methods, presenting and discussions wrapped in the socialization of BPJS Ketenagakerjaan to UMKM agents in the Medokan Ayu, Surabaya, or in the world of marketing, BPJS Ketenagakerjaan conducts direct selling to prospective consumers through secondary socialization to UMKM agents in Medokan Ayu, Surabaya which is also a research internship activity